Acaricidal activity of Alstonia scholaris and Sida cordifolia leaf extracts against Hyalomma anatolicum ticks - GODARA, R; RAFIQI, S I; SHARMA, R; KATOCH, R; YADAV, A; PILANIA, P K; VERMA, P K (The Indian Journal of Animal Sciences, 2021)
Development of acaricidal resistance and environmental pollution has driven need for eco-friendly pesticides and herbal acaricides. Leaf extracts of Alstonia scholaris and Sida cordifolia in four different solvents were used in the range of 0.25-8.0% for larval immersion test against unfed larvae of Hyalomma anatolicum. Mortality rates of larval ticks were in dose-dependent manner ranged from 0.5 to 100% for A. scholaris and from 0.8 to 100% for S. cordifolia. Acetone extract of A. scholaris and methanolic extract of S. cordifolia were most effective against larval ticks with LC50 values of 0.71% and 0.42%, respectively. Significant larvicidal activity of A. scholaris and S. cordifolia leaf extracts against unfed larvae of H. anatolicum qualify them as green pesticides which could be combined with other tools for integrated pest management.